Decrease in Local Volumetric Bone Mineral Density in Osteoarthritic Joints Is Associated with the Increase in Cartilage Damage: A Peripheral Quantitative CT Study - Tamaddon, Maryam; Chen, Shen Mao; Vanaclocha, Leyre; Hart, Alister; El-Husseiny, Moataz; Henckel, Johann; Liu, Chaozong (Frontiers in Materials, 2017)
Osteoarthritis (OA) is one of the most prevalent joint diseases, which causes pain and disability in the adult population. OA affects the osteochondral unit in the joints, which comprises both cartilage and subchondral bone. There has been some progress in understanding the changes in subchondral bone with progression of OA. However, local changes in subchondral bone such as microstructure or volumetric bone mineral density (vBMD) in connection with the defect in cartilage are relatively unexplored. To develop an effective treatment for progression of OA, it is important to understand how the physical environment provided by the subchondral bone affects the overlying cartilage. In this study, we examined the vBMD distribution in the OA joint tissues obtained from total hip replacement surgeries due to OA, using peripheral quantitative CT (pQCT). It was found that there is a significant decrease in vBMD, which co-localizes with the damage in the overlying cartilage. This was not limited to the subchondral bone immediately adjacent to the cartilage defect but continued in the layers below. Bone resorption and cyst formation in the OA tissues were also detected. We observed that the bone surrounding subchondral bone cysts exhibited much higher vBMD than that of the surrounding bones. pQCT was able to detect significant changes in vBMD between OA and non-OA samples, as well as between areas of different cartilage degeneration, which points to its potential as a technique for detection of early OA.